Pelatihan Pengembangan Inovasi Pembelajaran Matematika Melalui Perangkat Lunak Microsoft Mathematics dan GeoGebra Bagi Guru SMA dan SMP di Wilayah Kota Kefamenanu dan Noemuti - Elinora Naikteas Bano; Fried Markus Allung Blegur; Grandianus Seda Mada; Eva Binsasi (LPPM Universitas Timor, 2022)
In 2019, average score for high school Mathematics for all modes of the national level examination was the lowest compared to other subjects in all majors. For the North Central Timor Regency, average Mathematics Test Score for the Science major is 31.08, the lowest of other subjects. In dealing with this problem, teachers need a learning innovation that allows students to learn mathematics with visualizations that are easy to make, easy to use, and attractive, as well as strong interaction between teachers and students to facilitate the transmission of concept understanding from teachers to students. Therefore, several schools in the city area in ​​Kefamenanu and Noemuti were selected and trained using Microsoft Mathematics GeoGebra software and continued with training to solve various mathematical problems using Microsoft Mathematics GeoGebra. Training activities began with an introduction to Microsoft Mathematics and GeoGebra and continued with solving various mathematical problems using Microsoft Mathematics and GeoGebra. Then proceed with follow-up activities in the form of mentoring. After training, 57.14% have used Microsoft Mathematics and 52.38% have used GeoGebra as a learning method in the classroom.